Hypertension and COVID-19: Ongoing Controversies - Tadic, Marijana; Saeed, Sahrai; Grassi, Guido; Taddei, Stefano; Mancia, Giuseppe; Cuspidi, Cesare (Frontiers in Cardiovascular Medicine, 2021)
Coronavirus disease 2019 (COVID-19) has become a worldwide pandemic responsible for millions of deaths around the world. Hypertension has been identified as one of the most common comorbidities and risk factors for severity and adverse outcome in these patients. Recent investigations have raised the question whether hypertension represents a predictor of outcome in COVID-19 patients independently of other common comorbidities such as diabetes, obesity, other cardiovascular diseases, chronic kidney, liver, and pulmonary diseases. However, the impact of chronic and newly diagnosed hypertension in COVID-19 patients has been insufficiently investigated. The same is true for the relationship between blood pressure levels and outcomes in COVID-19 patients. It seems that the long discussion about the impact of angiotensin-converting enzyme inhibitors (ACEI) and blockers of angiotensin I receptors (ARB) on severity and outcome in COVID-19 is approaching an end because the large number of original studies and meta-analyses discarded the initial findings about higher prevalence of ACEI/ARB use in patients with unfavorable outcomes. Nevertheless, there are many controversies in the relationship between hypertension and COVID-19. The aim of this review article is to provide a clinical overview of the currently available evidence regarding the predictive value of hypertension, the effect of blood pressure levels, the impact of previously known and newly diagnosed hypertension, and the effect of antihypertensive therapy on the severity and outcomes in COVID-19 patients.